Comparative thermodynamic analysis of an improved ORC process with integrated injection of process fluid. (1st March 2023) - Krail, Jürgen; Beckmann, Georg; Schittl, Florian; Piringer, Gerhard
Abstract: In contrast to water-steam Rankine cycles, the ORC process uses organic working fluids. For working fluids of the dry class, a recuperator heat exchanger is frequently installed to increase the cycle efficiency. This paper analyses an improved ORC process with these features: A liquid working fluid stream is injected into the vapour flow between the high-pressure and the medium-pressure stage of the turbine. Furthermore, the recuperator is replaced by a spray condenser. The main objective is to increase efficiency with moderate changes in the process layout. A thermodynamic comparison of the improved process with a state-of-the-art ORC process is carried out by simulations and optimisations. A significant efficiency gain for the improved ORC process is obtained by a combination of the aforementioned features, mainly because of an increase of the mass flow in the economiser of the vapour generator (better heat utilization) and a corresponding mass flow in the medium stage of the turbine (additional power production). As a use case, waste heat utilization from a clinker cooler at a temperature level of 275 °C was simulated. The improved process would lead to a significant increase in the overall net efficiency by up to 14%, compared to a state-of-the-art ORC process.